Evolutionary remnants as widely accessible evidence for evolution: the structure of the argument for application to evolution education - Warren D. Allmon; Robert M. Ross (Evolution: Education and Outreach, 2018)
Abstract Evolution education, in both schools and informal education, often focuses on natural selection and the fit of organisms through natural selection to their environment and way of life. Examples of evidence that evolution has occurred are therefore often limited to a modest number of classic but exotic cases, with little attention to how one might apply principles to more familiar organisms. Many of these classic examples are examples of adaptation; adaptation to local environments is, however, an outcome that could in principle also be explained by supernatural creation or design. A frequent result is the perception among the public is that examples of evolution are rare, and that the existence of well-adapted organisms may just as easily be explained metaphysically. We argue that among categories of evidence of evolution accessible to non-specialists in any environment, the most compelling evidence of common ancestry consists of remnants of evolutionary history evident in homologous features, particularly when those homologies are related to lack of fit of organisms to their way of life (“vestiges”) or to better fit that involves complicated combinations of parts usually assigned other functions (“contrivances”). Darwin emphasized the critical nature of this argument from imperfections, and it has been part of traditional catalogs of “evidence for evolution” for more than a century. Yet while remnants of history are widely used as a category of evidence for evolution, their utility in education of comparative anatomy to document body parts passed on through descent is underemphasized in evolution education at all levels. We explore the use of evolutionary remnants to document common ancestry and evidence for evolution, for application to evolution education.